Production Layout Design for Modified Cassava Flour-Based Product - Anas Saifurrahman; Yun Prihantina Mulyani; Annisa Dewi Akbari; Ahmad Arwyn Imamur Rozi (Jurnal Inotera, 2023)
Having an increasing trend in demand for healthy food and the government's support in meeting the cassava needs, this study aims to improve the scale of production of Modified Cassava Flour (MOCAF) by applying the systematic layout planning (SLP) method. This method is used to review the existing conditions of the production process and design a new layout for scaling up production. The result of the new layout is an ideal condition and a stable production target, but it is implemented gradually. By adopting systematic layout planning, it is expected to improve production efficiency and optimize resource utilization. This study provides useful information for the food industry in improving Mocaf production scale and can also contribute to research on production management and production layout